IbM KELOMPOK USAHA KECIL KACANG ASIN DESA TROWULAN KECAMATAN TROWULAN MOJOKERTO - Puji Slamet; Erni Puspanantasari Putri (JPM17: Jurnal Pengabdian Masyarakat, 2015)
Trowulan is one of the tourist areas of history that have excellent potential in Mojokerto regency. As relics of the kingdom Mojopahit area, potentially Tourism Trowulan visited by domestic tourists and international tourists. People living in tourist areas generally work as traders in both the small-scale micro-scale mauun engaged in the provision of a small meal as food supplement for the tourists also partly used as souvenirs. among small food businesses in this area are small businesses owned Sofuan father and Mr. Fahturozy in the village Trowulan, Trowuln districts in Mojokerto. Small enterprises salted peanuts belong to Mr. Sofyan established since 2000, and until now only able to produce as much as 15 kg of salted peanuts per day to be done by 3 people. An average ability in the epidermis peeling beans in a day not more than 5 kg. The same was experienced by small businesses owned by Mr. Muhammad Fahturozy established since 2002 and is only able to produce about 9 kg of salted peanuts per day worked 2 workers. Information from both these business owners, the actual demand for salted peanuts very much but can not meet because of limited manpower and costs for peeling the the cuticle nuts.Based on that information we try to provide a way out by trying to use a peeler peanut the cuticle so that the amount of production can be increased. IbM 2015 through this program can be realized both small businesses desire the salted peanuts. Peeler the cuticle beans that have been tested turned out to show a significant result is a tool that are received by the father and the father of Muhammad Fahturozy Sofuan can produce 19-20 kg/ h with the percentage of broken nuts Â± 5%. New problems that occurred with increasing the ability of the cuticle peeling is the lack of means of frying beans so the beans peeled produced can not immediately fried. It was found to affect the quality of the peanuts produced. With the desire and high spirits of both small businessmen salted peanuts on the quality of their products, they are willing to pay to add frying pan so that the quality of salted peanuts produced is maintained. Increasing the number of salted peanut production is certainly an impact on the marketing of the bean. The solution we provide to overcome the problems of marketing is to provide guidance and assistance in an effort to increase the number and expand the marketing area. Guidance we have done is to give a tutorial on how to market the salted peanuts and how to get new customers. The results of the guidance is the addition of marketing area that was originally only in the area of Mojokerto, now began to be marketed in Jombang, Sidoarjo and Gresik. The second desire of small entrepreneurs salted peanuts to be able to market their products in the mini market and super market while it is still constrained in handling brand and IRT permits are still sought. Besides problems IRT licenses and brands that are still in the maintenance effort, there is still another problem that needs to be thought of looking for a way out is the speed of packaging and packaging quality to make it look more attractive in addition to maintaining a stable taste quality.Keywords: Small enterprises Salted peanuts, IbM Partners, Parer the porters epidermis beans